UPPER MANTLE STRUCTURE BENEATH CENTRAL SIBERIA AND NEIGHBORING REGIONS, FROM PP-P TOMOGRAPHY - Bushenkova N.A.; Tychkov S.A.; Kulakov I.Yu. (My University, 2003)
A new teleseismic tomography approach (RR-R scheme), based on joint processing of differential travel times of P or S refracted rays and corresponding PP or SS rays with bounce points in a selected area, allows three-dimensional velocity images of upper mantle in aseismic regions with poor seismological coverage. The approach makes it possible to avoid the difficulty of source and station corrections which cause problems in teleseismic tomography. The RR-R scheme has been applied to more than 10,000 ray pairs from the ISC database to investigate a large region from the North Arctic Ocean to northern China and Mongolia. Inversion was carried out in several separate windows that cover the study territory, and velocity anomalies were computed in grid nodes distributed in the 3D region according to ray density. The results from different windows were synthesized into general maps and cross sections. The lithospheric structure imaged by the inversion includes positive P-wave velocity anomalies associated with the Precambrian Siberian craton and Tuva and negative anomalies corresponding to the thin lithosphere of the West Siberian Plate, and an intense negative anomaly beneath the Hangayn mountains, possibly, produced by a mantle plume.
Keywords: Three-dimensional velocity structure; PP waves; RR-R scheme; lithospheric thickness; plume; Central Siberia; Altai; Hangayn